EFEITOS DA SUBSTITUIÇÃO DO MILHO PELO SORGO, COM ADIÇÃO DE ENZIMAS DIGESTIVAS, SOBRE O GANHO MÉDIO DE PESO DE FRANGOS DE CORTE - MORAIS, E.; FRANCO, S. G.; FEDALTO, L. M. (Archives of Veterinary Science, 2002)
O presente experimento foi realizado na Estação Experimental do Cangüiri, com a finalidade de se avaliar os efeitos do sorgo usado em substituição ao milho, com adição de enzimas digestivas, sobre o ganho médio de peso (GMP) de frangos de corte. As aves foram criadas em três fases de alimentação: 0- 21 (fase inicial), 22- 42 (fase de crescimento) e 43 49 dias (fase final). Foram utilizados quatro níveis de sorgo (0, 15, 30 e 45%) em substituição ao milho, com adição de três níveis de enzimas (0, 750 e 1.500gE/ton de ração), sendo três repetições por tratamento, em um delineamento experimental totalmente casualizado. Aos 21 dias, o ganho médio de peso (GMP), com utilização de 45% sorgo, foi melhor que 30 e 15%; no entanto, estes três níveis não diferiram da ração sem sorgo. Aos 42 e 49 dias os resultados de GMP não se mostraram consistentes com aqueles da primeira fase. Contudo, o sorgo não exerceu efeito negativo sobre os resultados, pois estes foram semelhantes àqueles com dietas a base de milho. Pode-se observar que até ao nível de 45% de substituição, o sorgo não interfere no ganho de peso das aves, concluindo-se que a adição de enzimas, nos níveis utilizados, também não teve influencia sobre esta variável. Effects on the weight gain of chikens by substitution of corn by sorghun and addition of digestive enzymes to the ration Abstract The present experiment was carried out at the Federal University of Paraná Experimental Station of Canguiri between 10/15/1997 and 12/04/1997. The main aim of the experiment was to evaluate the effect of sorghun as a substitute of corn on the mean weight gain of chicken. The experiment was carried out with addition of digestive enzymes. The chicken were raised in 3 feeding phases: 0-21 days (initial phase), 22-42 days (growing phase) and 43-49 days (final phase). Four levels of sorghun - 0, 15, 30 and 45 % - were used in order to substitute corn in the diet, with the addition of 3 levels of digestive enzymes (0, 750 and 1500 g E/per ton of ration. The experiment was carried out with a total of 3 repetitions of each treatment following a total casually experimental delineation. On the 21st day it has been found that the main weight gain of the chickens fed with 45% of sorghun was superior than the gain weight found for the chickens fed during 30 days with the ration containing 15% of sorghun. As for the 3 levels of enzymes used, no difference has been found in the weight gain in regard to the diet without sorghun. the results on days 42 and 49 were not consistent with the experimental results of the first phases, but sorghun did not show any negative effect , considering that the results thus obtained were similar to the ones obtained with only corn containing rations. Another important observation is that up to the level of substitution of 45% sorghun did not interfere with the chicken weight gain. This observation allows the conclusion that digestive enzymes addition the diet did not influence the gain weight.